2018
DOI: 10.1021/acsomega.8b03006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Small Molecules (H2, CO2, N2O, CH4, and C6H6) by a Porphyrinoid-Based Dimagnesium(I) Complex, an Electride

Abstract: A density functional theory-based computation has been carried out to reveal the geometrical and electronic structures of Mg 2 EP ( 1 ), where EP is an extended (3.1.3.1) porphyrinoid system. EP is a 22 π electronic system and is aromatic in nature. Here, we have studied the thermodynamic and kinetic stabilities of EP 2– -supported Mg 2 2+ ion. The nature of bonding has been studied using natural bond orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…The α value of [Mg 4 ( Dipp H L) 2 ] 2– complex is much higher as compared to the previous systems and the γ ∥ values are almost comparable to them. The increased α value for the [Mg 4 ( Dipp H L) 2 ] 2– can be attributed to the double number of Mg–Mg bonds as compared to that in the Mg 2 EP complex (see Table S7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The α value of [Mg 4 ( Dipp H L) 2 ] 2– complex is much higher as compared to the previous systems and the γ ∥ values are almost comparable to them. The increased α value for the [Mg 4 ( Dipp H L) 2 ] 2– can be attributed to the double number of Mg–Mg bonds as compared to that in the Mg 2 EP complex (see Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray diffraction data in conjunction with computational study of the β‐diketiminate ligand stabilized dimeric magnesium(I) complexes have shown the existence of NNA near the middle of the two bonded Mg(I) centers . Recently some of us have shown by theoretical work that a cyclic (3.1.3.1) porphyrinoid based tetradentate anionic ligand can stabilize the Mg 2 2+ ion . The complex has fulfilled all criteria and classified as an electride material which can activate small molecules like H 2 , CO 2 , N 2 O, CH 4 , C 6 H 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we have studied several molecules (see Figure 1 for the molecular representation of the systems) that were already classified as molecular electrides following the criteria we established: 45 Li@calix [4]pyrrole, 45,70,87 Na@calix [4]pyrrole, 88 TCNQLi 2 , 45,89 TCNQNa 2 , 45,89 TCNENa 3 , 90 TCNENa 4 (II), 90 Mg 2 EP, 91 Mg 2 @C 60 , 88 , and e@C 60 F 60 . 45,92 Namely, all of these systems present at least a NNA, a highly localized density in the region of the NNA -indicated by the large negative value of the Laplacian of the electron density 79 or the presence of an ELF 51,74 basin-and large nonlinear optical properties (NLOPs).…”
Section: Methodsmentioning
confidence: 99%
“…For TCNENa 3 , additional calculations with CCSD and CCSD(T) were also included to assess the performance of MP2, which is the reference for all the other systems. In order to confirm the single-reference nature of TCNENa 3 , we performed T1, 101 and D1 diagnostics 102 on Figure 1: Molecular representations of Li@calix [4]pyrrole, 45,70,87 Na@calix [4]pyrrole, 88 TCNQLi 2 , 45,89 TCNQNa 2 , 45,89 TCNENa 3 , 90 TCNENa 4 (II), 90 Mg 2 EP, 91 Mg 2 @C 60 , 88 and e@C 60 F 60 45,92 optimized at the CAM-B3LYP/ma-TZVP level of theory. Molecules with an M atom have been optimized and studied for M=Li and M=Na.…”
Section: Methodsmentioning
confidence: 99%